On Culture, Values, and Peace (Selected Essays and Letters) - Nicholas Roerich (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2018)
1. The Banner of Peace 2. The Sacred Sign of Peace 3. The Heart of Culture 4. The Red Cross of Culture 5. The Mission of Womanhood 6. Glory to Women, Bearers of Culture 7. Roots of Culture 8. In spite of difficulties (To the Bulgarian Society, 1930) 9. Re-evaluation 10. Defense of Values